2020
DOI: 10.1161/jaha.120.016495
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Comparison of Ticagrelor Monotherapy Versus Ticagrelor and Aspirin in Patients After Percutaneous Coronary Intervention: The TEMPLATE (Ticagrelor Monotherapy and Platelet Reactivity) Randomized Controlled Trial

Abstract: Background To assess differences in platelet inhibition during ticagrelor monotherapy (TIC) or dual therapy with ticagrelor and aspirin (TIC+ASP) in patients after percutaneous coronary intervention using a comprehensive panel of functional tests. Methods and Results In a single‐center parallel group, open label, randomized controlled trial, 110 participants were randomized to receive either TIC (n=55) or TIC+ASP (n=55) for 4 weeks. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The TEMPLATE (Ticagrelor Monotherapy and Platelet Reactivity) trial, a study investigating the pharmacodynamic differences between ticagrelor monotherapy versus ticagrelor and aspirin in patients after PCI, demonstrated similar levels of inhibition of most platelet activation pathways with ticagrelor compared with DAPT; however, a greater aggregation response was seen with a collagen activation marker, demonstrating an incomplete inhibition of glycoprotein VI (collagen) receptor-mediated platelet activation with ticagrelor alone as compared to DAPT. This difference in response can offer a pharmacodynamic explanation in the lower bleeding rates observed in our meta-analysis and recent trials [ 15 ]. However, the observed reduction in all-cause death may have more than one explanation and non-analyzed myocardial infarction in the TICO trial may have impacted on the mortality outcome.…”
Section: Discussionsupporting
confidence: 58%
“…The TEMPLATE (Ticagrelor Monotherapy and Platelet Reactivity) trial, a study investigating the pharmacodynamic differences between ticagrelor monotherapy versus ticagrelor and aspirin in patients after PCI, demonstrated similar levels of inhibition of most platelet activation pathways with ticagrelor compared with DAPT; however, a greater aggregation response was seen with a collagen activation marker, demonstrating an incomplete inhibition of glycoprotein VI (collagen) receptor-mediated platelet activation with ticagrelor alone as compared to DAPT. This difference in response can offer a pharmacodynamic explanation in the lower bleeding rates observed in our meta-analysis and recent trials [ 15 ]. However, the observed reduction in all-cause death may have more than one explanation and non-analyzed myocardial infarction in the TICO trial may have impacted on the mortality outcome.…”
Section: Discussionsupporting
confidence: 58%
“…In the presence of potent P2Y 12 blockade, in vitro pharmacodynamic investigations have shown that aspirin does not provide much additional antiplatelet effect [ 29 ]. This was also confirmed in a series of ex vivo pharmacodynamic studies [ 30 , 31 , 32 ]. While withdrawal of aspirin indeed eliminates its specific inhibitory effects mediated by the COX-1 pathway, other platelet signaling pathways are still affected by potent P2Y 12 blockade [ 20 , 33 ].…”
Section: Rationale For P2y 12 Inhibitor Monotherapysupporting
confidence: 59%
“…The success of P2Y12 inhibitor monotherapy was not a coincidence. Many in vitro and ex vivo investigations have shown that aspirin provided very limited additional platelet inhibition and anti-thrombotic effect to a potent P2Y12 inhibitor [28][29][30]. Of note, most of the patients treated with P2Y12 inhibitor monotherapy were using ticagrelor.…”
Section: Discussionmentioning
confidence: 99%